Knowledge of Gujjar and Bakarwals Regarding Improved Livestock Management Practices (Indian Journal of Extension Education, 2014)
Gujjar and Bakarwal constitute the two major nomadic tribal groups of Jammu and Kashmir. Both these tribal groups have livestock rearing as the prime vocation. Whereas, Gujjars possess large herds of buffaloes, Bakarwals are associated with goat and sheep rearing. Both these tribal group play a crucial role in meeting the requirement of milk and meat for the cities and towns and hence contribute significantly to the livestock sector of the state. Traditionally both these tribes are nomadic in nature. They have seasonal migration from the plains of Jammu region to the upper reaches of Kashmir valley. The study has revealed that fropal population lack knowledge regarding various aspects like identification of discase, clean milk production improved breed of cattle, importance of mineral supplementation etc.